Connection, Engagement, and Belonging: Exploring Young Women’s Positive Experiences for Building Inclusive STEM Classrooms - Saville, Elizabeth; Cherkowski, Sabre; Jakobi, Jennifer (Alberta Journal of Educational Research, 2023)
This qualitative study was designed from an appreciative and positive research focus to examine how and why young women engage in, succeed, and persevere in STEM courses. The objective was to gain student perspectives on improving gender equality in STEM education. From the questionnaire and focus groups with participating women university students enrolled in STEM courses three themes emerged (a) Relational Connection with teachers and/or students, (b) Engagement with STEM Curriculum that reflected influential pedagogical learning cultures, and (c) Cultures of Belonging and inclusion. This research offers insight into positive factors for women’s success in STEM academics and careers. Keywords: Female students in STEM; STEM Education; STEM Engagement; Inclusivity; Gender Bias Cette étude qualitative a été conçue dans une optique de recherche appréciative et positive afin d'examiner comment et pourquoi les jeunes femmes s'engagent, réussissent et persévèrent dans les cours de science, technologie, ingénierie et mathématiques (STIM). L'objectif était d'obtenir le point de vue des étudiantes sur l'amélioration de l'égalité des sexes dans l'enseignement des STIM. Le questionnaire et les groupes de discussion auxquels ont participé des étudiantes universitaires inscrites à des cours de STIM ont permis de dégager trois thèmes : (a) le lien relationnel avec les enseignants et/ou les étudiants, (b) l'engagement dans le programme de STIM qui reflète des cultures d'apprentissage pédagogiques influentes, et (c) les cultures d'appartenance et d'inclusion. Cette recherche offre un aperçu des facteurs positifs pour la réussite des femmes dans les études et les carrières en STIM. Mots clés : étudiantes dans les STIM ; éducation aux STIM ; engagement dans les STIM ; inclusion ; préjugés sexistes